Healing after horizontal root fractures: 3 cases with 2-year follow-up - Yoorina Choi; Sung-Ok Hong; Seok-Ryun Lee; Kyung-San Min; Su-Jung Park (Korean Academy of Conservative Dentistry, 2014)
Among dental traumas, horizontal root fractures are relatively uncommon injuries. Proper initial management and periodical evaluation is essential for the successful treatment of a root-fractured tooth. If pulpal necrosis develops, endodontic treatment is indicated, exclusively for the coronal fragment. Fragment diastases exert a great influence on healing at the fracture line and on pulpal necrosis. An adequately treated root-fractured tooth has a good prognosis. This case report describes the treatment and 2-yr follow up of 3 maxillary central incisors, first with horizontal root fracture, second with horizontal root fracture and avulsion, and third with horizontal root fracture and lateral luxation. All three cases were treated with mineral trioxide aggregate (ProRoot, Dentsply). During 2 yr of follow-up evaluation, the root-fractured teeth of the present patients were well retained in the arch, showing periodontal healing, even after endodontic treatment.